2002
DOI: 10.1080/00984100290071333
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcomes in the Women of the Red River Valley of the North. I. The Spouses of Pesticide Applicators: Pregnancy Loss, Age at Menarche, and Exposures to Pesticides

Abstract: In the current study, there was a modest but significant increase in risk (1.6- to 2-fold) for miscarriages and/or fetal loss occurring throughout the year in the spouses of applicators who use fungicides. There is a surprisingly significant deficit in the number of male children born to the spouses of fungicide applicators. First-trimester miscarriages occur most frequently in the spring, during the time when herbicides are applied. Use of sulfonylurea (odds ratio OR = 2.1), imidizolinone (OR = 2.6) containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…In the present, smaller-scale but more detailed study, fungicide use by the male pesticide applicator parent was associated with fewer male births, most significant among children with birth defects. Similarly, the spouse of the pesticide applicator who applied or used fungicides on the farmstead is at a significantly higher risk for a first trimester miscarriage (4). The majority of these fungicide applications cited were conducted by air.…”
Section: Sex and Sex Ratio Of Children Born To Applicator Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present, smaller-scale but more detailed study, fungicide use by the male pesticide applicator parent was associated with fewer male births, most significant among children with birth defects. Similarly, the spouse of the pesticide applicator who applied or used fungicides on the farmstead is at a significantly higher risk for a first trimester miscarriage (4). The majority of these fungicide applications cited were conducted by air.…”
Section: Sex and Sex Ratio Of Children Born To Applicator Familiesmentioning
confidence: 99%
“…Live births and children with birth defects were defined by written survey. Findings regarding pregnancy losses, including miscarriages, are discussed elsewhere (4). In the present effort, birth defects occurring in a total of 1,532 live births were considered in these analyses.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Pesticide exposure among men has been associated with increased sperm abnormalities (13), while studies have reported spontaneous miscarriages among pesticide-exposed women (6,14). Birth defects have been reported in cases where either men or women were exposed to pesticides (15,16).…”
mentioning
confidence: 99%
“…Occupational exposures and activities are increasingly linked to adverse reproductive outcomes in working populations (1)(2)(3)(4)(5)(6)(7)(8). Occupational exposures associated with adverse reproductive outcomes include increased risks for spontaneous miscarriages among (i) healthcare workers exposed to chemicals including disinfectants, antineoplastic, and anesthetic drugs and (ii) women in industry exposed to heavy metals and solvents (9).…”
mentioning
confidence: 99%
“…Working with or applying pesticides, primarily in agricultural and horticultural settings, appears to consistently reduce fertility and fecundability (147)(148)(149)(150)(151)(152). Preconception exposure, but not exposure during pregnancy (153), appears to elevate risk for spontaneous abortion (154).…”
Section: Reproductive Effects Of Adult Exposuresmentioning
confidence: 99%